The fitness of chemotrophs increases when their catabolic by‐products are consumed by other species. (14th October 2019) - Seto, Mayumi; Iwasa, Yoh
Abstract: Chemotrophic microorganisms synthesise biomass by utilising energy obtained from a set of chemical reactions that convert resources to by‐products, forming catabolic interactions. The amount of energy obtained per catabolic reaction decreases with the abundance of the by‐product named as the 'abundant resource premium'. Consider two species, Species 1 and 2, Species 1 obtains energy from a reaction that converts resource A to by‐product B. Species 2 then utilises B as its resource, extracting energy from a reaction that converts B to C. Thus, the presence of Species 2 reduces the abundance of B, which improves the fitness of Species 1 by increasing the energy acquisition per reaction of A to B. We discuss the population dynamic implication of this effect and its importance in expanding a realised niche, boosting material flow through the ecosystem and providing mutualistic interactions among species linked by the material flow. Introducing thermodynamics into population ecology could offer us fundamental ecological insights into understanding the ecology of chemotrophic microorganisms dominating the subsurface realm. Abstract : We developed a simple mathematical model for a microbial mutualistic interaction in which the catabolic by‐product of the first species is utilized as a catabolic resource by the second species (a non‐feeding catabolic interaction), which has been neglected in theoretical ecology. Our modeling study shows how the consumption of the by‐product of species by others reduces the minimum energy demand for persistence, expands the realized niche, and boosts material flow.